Pelaksanaan Event Sponsorship Sebagai Implementasi Komunikasi Pemasaran Produk By.U Oleh Telkomsel Branch Surabaya - Sabhina Agni Naenara; Yanda Bara Kusuma (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Currently, there are many internet providers in Indonesia that offer various benefits, such as digital providers. Demand for the internet continues to increase every year. by.U is the first digital provider in Indonesia targeting the millennial or Gen Z demographic, which has attracted researchers' interest in conducting further research about the company. Researchers used a qualitative approach known as a case study which aims to study the marketing communication methods and promotional mix used by Telkomsel to promote by.U cards to the youth market. Interviews, documentation of event implementation, and observations were carried out to collect data. The data processing method used by the author is descriptive. A brief description and analysis of data collected from various sources, both direct and indirect, is presented previously. The focus of this research is the process of implementing marketing communications by the by.U. company, the data for which was collected through interviews and observation. After that, the data will be analyzed in three stages: data reduction, data presentation, and conclusion drawing. Marketing communications used by event sponsors to increase sales of by.U products consist of sales promotions, personal sales and direct marketing. This research shows that by.U controls its marketing communications by using social media, influencers, and digital placements to make customers want to buy its products. In this research, marketing communication strategies include digital placement and influencer marketing.